Implementing a comprehensive research compliance program : a handbook for research officers - Dade, Aurali; Olafson, Lori, 1961-; DiBella, Suzan M. (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
The senior research compliance administrator has emerged as a critically important position as universities and other research organizations face an increasingly intricate regulatory environment. These administrators are tasked with a special challenge: ensuring that their institutions conduct safe, ethical, and compliant research while also helping researchers understand and meet compliance requirements and achieve their research goals. These competing responsibilities can make the role of the research administrator complex; however, those who serve in this role may find that they have limited preparation for the challenges and little or no formal education in the field.Thus, the goal of this handbook is to provide practical guidance to research administrators who are responsible for a wide variety of compliance programs. Previous volumes on these topics have focused primarily on educating research faculty, staff, and students. An assumption in many of these handbooks is that all additional questions related to research ethics and regulations should be directed to the senior research administrator; yet, the books have limited guidance intended for the senior research administrators themselves. This handbook is designed, therefore, to serve as a detailed program implementation manual for these administrators, who are expected to be conversant on a broad range of complex ethical and regulatory topics and to provide guidance to those conducting research, as well as upper administration and others interested in safe, ethical, and compliant research.
Keywords: Research -- United States -- Management -- Handbooks, manuals, etc.; Research grants -- United States -- Handbooks, manuals, etc.; Federal aid to research -- United States -- Handbooks, manuals, etc.; Compliance auditing -- United States -- Handbooks, manuals, etc.; Business & Economics -- Organizational Behavior.; Higher education, tertiary education.; Organizational theory and behaviour.; elektronické knihy; electronic books